Neuromarketing applied to tourism: An introductory vision - Chavaglia, J. N.; Filipe, J.; Ferreira, M. A. M. (Modeling and new trends in tourism: A contribution to social and economic development, 2017)
– Nowadays tourism has become so important that companies develop new strategies to meet the new market situations. Neuromarketing provides techniques to better understand the brain of travellers and supports the promotion of new developments for companies’ strategies. The competition in the tourism sector requires innovation in terms of sale and communication strategies. Neuromarketing may work as a tool by contributing for the understanding of the reasons and emotions that will guide tourists. This tool will allow them to get a final choice in terms of a particular service, by choosing it and not another one. Both, the tourist and the provider of services, will benefit from the use of neuromarketing techniques. In the present stage of tourism development, tourists’ fascination for many destinations in many different countries is important to define strategies. The considerable increase in tourism movements bring new companies to the marketing area to provide new services and complement the existing ones, finding out new offers through new products.